1992
DOI: 10.1111/j.1399-302x.1992.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of Actinobacillus actinomycetemcomitans based on analysis of 23S ribosomal RNA

Abstract: Actinobacillus actinomycetemcomitans is a key microorganism in the pathogenesis of several different forms of periodontal diseases. Identification of this bacterium from clinical specimens may often be complicated by the fact that the colony morphology on TSBV selective medium closely resembles that of Haemophilus aphrophilus and a key differentiating characteristic, catalase reaction, may be variable. Recent genetic studies have shown that the 23S ribosomal RNA molecule is split into two smaller forms in A. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Epidemiological studies of/), actinomycetemcomitans have suggested that the bacterium is primarily transmitted among family members in LJP families (Zambon etal. 1983, Okuda et al 1984, Preus & Olsen 1988, DiRienzo & Slots 1990, Alaluusua et al 1991. Preus et al 1993, Offenbacher et al 1985 and in families with general adult periodontitis (Petit e( al.…”
Section: Actinohacillusmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies of/), actinomycetemcomitans have suggested that the bacterium is primarily transmitted among family members in LJP families (Zambon etal. 1983, Okuda et al 1984, Preus & Olsen 1988, DiRienzo & Slots 1990, Alaluusua et al 1991. Preus et al 1993, Offenbacher et al 1985 and in families with general adult periodontitis (Petit e( al.…”
Section: Actinohacillusmentioning
confidence: 99%
“…Subgingival bacterial plaque was obtained from all subjects by placing one paper point for 10 s into the mesial sulci/pockets of all teeth and if present, any additional sites with pockets of ^5 mm (Preus et al 1994). In edentulous patients sterile cotton swabs were gently brushed against the inner buccal mucosa and dorsum of the tongue.…”
Section: Isolation Of Individual Strains Of a Actinomycetemcorrtltansmentioning
confidence: 99%
“…All 42 test strains had been identified by colony morphology and catalase test on a selective medium. The preliminary identification was verified by fermentation of selected sugars as well as rapid rRNA assay [18], and the serotype of each strain determined by indirect immunofluorescence using serotype-specific antisera [19]. All 1 strains were grown at 37°C for 48 h in 100 ml of strength Brain Heart Infusion (BHI) broth containing 5 mg/1 hemin, 1 g/l sodium bicarbonate and 10 gg/ml vitamin K1, in an atmosphere of 5% CO 2 in air.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…All 1 strains were grown at 37°C for 48 h in 100 ml of strength Brain Heart Infusion (BHI) broth containing 5 mg/1 hemin, 1 g/l sodium bicarbonate and 10 gg/ml vitamin K1, in an atmosphere of 5% CO 2 in air. The cells were pelleted and checked for purity [18], and chromosomal DNA was extracted from each of the A. actinomycetemcomitans strains as described previously Growth and purification of bacteriophage 4a Aa Bacteriophage d~Aa was grown in its indicator strain A. actinomycetemcomitans 29524, and purified using a modification of the procedure pre- were identified by comparing the electrophoretic pattern of the restriction fragments with that obtained from HindlII digestion of purified cbAa DNA. The phage 4)Aa HindlII fragment F was isolated from the agarose gel by electroelution and used in preparing the phage-specific probe.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…Despite the lack of a complete genomic sequence, IDH781, a rough strain, is commonly used as a model for pathogenesis and basic bacteriology studies (311). Rough strains of A. actinomycetemcomitans display the classic star-shaped colony morphology observed in clinical isolates from LAP patients, so they are more appropriate for the study of A. actinomycetemcomitans biology than those displaying a smooth colony phenotype (12, 13). …”
Section: Genome Announcementmentioning
confidence: 99%